The effect of helium implantation on the deformation behaviour of tungsten: X-ray micro-diffraction and nanoindentation. (15th March 2018) - Das, S.; Armstrong, D.E.J.; Zayachuk, Y.; Liu, W.; Xu, R.; Hofmann, F.
Abstract: The effect of helium-implantation-induced defects on deformation behaviour is examined by comparing spherical nano-indents in unimplanted and helium-implanted regions of a tungsten single crystal. Helium-implantation increases hardness and causes large pileups. 3D-resolved X-ray micro-diffraction uniquely allows examination of the complex lattice distortions beneath specific indents. In the ion-implanted material we find reduced lattice rotations and residual strains due to indentation, indicating a more confined plastic zone. Together, our observations suggest that helium-induced defects initially act as efficient obstacles to dislocation motion, but are weakened by the subsequent passage of dislocations, causing a reduction in work hardening capacity. Graphical abstract: Image 2